Relevance of ecocriticism (Revista de Crítica Literaria Latinoamericana, 2014)
The pertinence of ecocriticism is due, to a large extent, to the fact that two divergent interests converge in it: on the one hand, the concern about models of environmentally sustainable development; on the other, the concern about the impact of the ecological crisis on the transformation and reading of linguistic universes, and on the ways literature represents ecosystems. Founded on ecological commitment, ecocriticism brings into focus the dialectics affecting the topic of the social engagement of literature, and it provides the opportunity to surpass its polarized treatment, the conceptual oppositions akin, and the binary logic sustaining it. Theoretical speculation and critical practice should take advantage of such opportunity not only in the frame of neo-indigenous Latin American literature, but also in the wider context of the national literatures written in Spanish in both sides of the Atlantic Ocean.
Keywords: ecocriticism; Hispanism; binary logic; engagement; Atlanticism